Abnormal formation of medial cord of brachial plexus - A case report - Rupak Jyoti Baishya; Rubi Saikia; Shobhana Medhi (Wolters Kluwer Medknow Publications, 2016)
Brachial plexus is the plexus of nerves that supplies the upper limb. The anterior divisions of upper and middle trunks form lateral cord and that of the lower trunk form medial cord. Posterior divisions of all the three trunks form the posterior cord. Here we report a case of unilateral variation in the formation of medial cord of brachial plexus during dissection of a female perinatal cadaver of 34 weeks of gestation which was dissected as a part of Congenital Malformation Survey conducted in the Department of Anatomy, Assam Medical College, Dibrugarh with necessary ethical clearance. Medial cord was formed by the anterior division of lower trunk and this cord had a communication from the posterior division of middle trunk. It is very important to be aware of the variations of the cords of the brachial plexus during different invasive procedures in that region